Putting consumers first [electricity supply industry]. - English, G. (IEEE spectrum)
All consumers-residential and commercial, small and large alike-are entitled to reliable, universal electricity service priced at a reasonable rate. This principle has been the bedrock of US state and federal regulation of the electric industry for decades, and, here, the author argues that it is being carelessly tossed aside in the name of ?competition? or ?choice?